THE IMPACT OF AN EDUCATIONAL CURRICULUM BASED ON THE FORREST MODEL REGARDING SOME MOTOR ABILITIES AND THE LEARNING OF THE ART OF STANDING ON THE FLOOR IN ARTISTIC GYMNASTICS FOR FEMALES - Ali Hussein, Abeer (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2025)
Artistic gymnastics floor shifts for female students. For the third portion, it involved creating a research population that included third-stage female students at Karbala University studying physical education, numbering (55) students. The sample was chosen by a simple random method, which divided it into two groups (experimental and control). The numbering process was as follows: (50) experimental samples were chosen, (5) were exploratory experiments, and the researcher selected (50) of the research sample. The variables of height, weight, and abilities were measured because of their association with height, weight, and the variables in the study, for the purpose of extracting the variance coefficient. To reveal and ensure the equality of the groups, the researcher employed the (t) test for both groups. It included the educational program for acquiring the researched ability as well as organizing activities within the educational program. The quantity of educational units was 8 and the duration of each was 90. The researcher's findings were as follows: the educational program had a positive effect on the development of motor skills, increased motivation, and saved time and energy. Creating an educational program using the Forrest model in regards to some motor abilities and learning the art of standing on the floor of the mat in women's artistic gymnastics. The results demonstrated that the students of the third stage have a preference for the learning style of the Forrest model in the development of motor abilities and the learning of the skill of standing on the mat in the practice of artistic gymnastics for females. The researcher suggested that it's more effective to focus on the pedagogical structure that promotes the student's learning according to their preferences, desires, and abilities. This will allow them to test their knowledge according to their wishes. It's more effective to conduct a similar investigation for other participants and students of physical education and sports science colleges.